Impact of climate factors on cyanobacterial dynamics and their interactions with water quality in South Taihu Lake, China. Issue 1 (2nd January 2017) - Baig, Shams Ali; Huang, Linglin; Sheng, Tiantian; Lv, Xiaoshu; Yang, Zhe; Qasim, Muhammad; Xu, Xinhua
ABSTRACT: Cyanobacterial bloom events in South Taihu Lake cause serious water quality problems and disturb aesthetic view of lake's environment. In this study, correlations between cyanobacterial blooms and hydro-meteorological factors, including water quality, temperature and precipitation were investigated. Results demonstrated that South Taihu Lake was heavily affected by cyanobacteria and the proliferation of cyanobacteria due to variations in hydro-meteorological factors and water quality conditions. Water quality parameters, including COD, NH3 -N, TN and TP improved significantly since 2008 even at an elevated cyanobacterial bloom situation. Correlation analyses have shown that the development of cyanobacterial density and chlorophyll a concentration was sensitive to a wider temperature variation. The optimum temperature for cyanobacteria was 20°C, while extremely low and high temperatures were found to suppress their growth. Moreover, unusual rainfall patterns were measured during the study period (2003–2009), which showed an adverse impact on cyanobacterial development. Findings from this study suggested that seasonal lake's water quality monitoring; suitable treatment of cyanobacterial blooms and strict policy implementation can solve the water quality issues in highly eutrophic lakes like Taihu.